Team commitment as a mediator between self-esteem and team climate as perceived by korean youth soccer players - Myungjin, J.; Sangwook, K.; Sungho, K. (Perceptual and Motor Skills, 2016)
This study examined whether team commitment mediates the relationship between self-esteem and perceived team climate in Korean youth soccer players. A total of 366 youth soccer players from the Korea football association participated in this study. Self-esteem and team commitment were found to significantly and positively affect perceived team climate; team commitment more strongly affected perceived team climate. Regarding structural relationships, self-esteem's direct effect on perceived team climate was not significant; however, self-esteem's indirect effect through team commitment was significant. Team commitment therefore mediated the relationship between self-esteem and perceived team climate. Metric invariance was supported for groups categorized by grade and key player, confirming that the model could be applied to various groups. ABSTRACT FROM AUTHOR